Religious Coexistence in the Dutch Republic and France in the Seventeenth Century: Legal Systems, Sacred Spaces, and Minority Resilience in Utrecht and Nîmes - Kang, Sukhwan (Journal of Early Modern Christianity, 2024)
This article examines religious coexistence and survival tactics of the religious minority groups in the Dutch Republic and the Kingdom of France, comparing Utrecht’s Catholics and Nîmois Huguenots in three respects: legal systems, battles over sacred spaces, and minority resilience. The distinct legal systems in the two countries - the Union of Utrecht and the Edict of Nantes - shaped two different forms of religious diversity in Utrecht and Nîmes, that is, de facto and de jure coexistence. Under these divergent legal settings, both Catholics and Protestants in the two cities similarly asserted their presence in the urban space and sought to practice their faith publicly. However, the minorities’ tactics in the conflicts over sacred spaces and the extent of physical violence in those battles differed significantly. While facing challenging circumstances in the last quarter of the seventeenth century, both minority groups demonstrated a remarkable resilience, mobilizing various survival tactics. They constantly negotiated the detailed conditions of coexistence with the dominant faith, attempting to carve out their own positions within their local, precarious environment.